2010
DOI: 10.1080/19440040903437865
|View full text |Cite
|
Sign up to set email alerts
|

Health economic impacts and cost-effectiveness of aflatoxin-reduction strategies in Africa: case studies in biocontrol and post-harvest interventions

Abstract: Advances in health economics have proven useful in evaluating the cost-effectiveness of interventions, where the benefit usually takes the form of improved health outcomes rather than market outcomes. We perform health-based cost-effectiveness analyses of two potential aflatoxin control strategies in Africa: 1) pre-harvest biocontrol, using atoxigenic strains of Aspergillus flavus to competitively exclude toxigenic strains from colonizing maize in Nigeria, and 2) postharvest interventions in a package to reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
167
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(175 citation statements)
references
References 37 publications
1
167
0
2
Order By: Relevance
“…Suboptimal postharvest conditions including handling, storage and processing have been suspect in playing a major role in aflatoxin accumulation in food crops within developing countries (Wu & Khlangwiset, 2010). Most households and traders in Kenya prefer polypropylene and polyethylene bags for packaging and storing peanuts with less than 1% of the traders storing their products in the recommended jute bags .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Suboptimal postharvest conditions including handling, storage and processing have been suspect in playing a major role in aflatoxin accumulation in food crops within developing countries (Wu & Khlangwiset, 2010). Most households and traders in Kenya prefer polypropylene and polyethylene bags for packaging and storing peanuts with less than 1% of the traders storing their products in the recommended jute bags .…”
mentioning
confidence: 99%
“…Peanuts and maize are the most susceptible crops to aflatoxin contamination (Wu & Khlangwiset, 2010). The two crops and their products are widely consumed in Kenya.…”
mentioning
confidence: 99%
“…There are four major aflatoxins, including B 1 , B 2 , G 1 , and G 2 ; however, aflatoxin‐B 1 is the most toxic and prevalent and is classified as a Group 1A carcinogen by the International Agency for Research on Cancer (IARC 2002). High‐dose exposure to aflatoxins concentrations can cause acute health effects such as vomiting, abdominal pain, and even possible death (Probst, Njapau, & Cotty, 2007; Sherif, Salama, & Abdel‐Wahhab, 2009), while sublethal chronic exposure may lead to liver cancer, stunting in children, and immune system suppression (Chan‐Hon‐Tong, Charles, Forhan, Heude, & Sirot, 2013; Wu & Khlangwiset, 2010). In 1981, for instance, the outbreak of aflatoxicosis as a result of ingestion of maize contaminated with 3.2–12 mg/kg of aflatoxin‐B 1 caused fatalities in Kenya (Obura, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In order to determine the cost effectiveness of various interventions, it is necessary to establish the cost effectiveness ratio (CER), which is the gross domestic product (GDP) multiplied by DALY saved per unit cost. In a study involving AF in maize in Nigeria and groundnut in Guinea, two strategies were compared viz: pre-harvest control; and post harvest interventions (Wu and Khlangwiset, 2010a). Accordingly, it was shown that the cost of both interventions exceeded the monetised values of lives saved and quality of life gained by reducing HCC, if applied nationwide.…”
Section: Possible Intervention Control Strategies For Af In Africamentioning
confidence: 99%